Recurrent Loss of SMARCA4 in Sinonasal Teratocarcinosarcoma. (October 2020) - Rooper, Lisa M.; Uddin, Nasir; Gagan, Jeffrey; Brosens, Lodewijk A.A.; Magliocca, Kelly R.; Edgar, Mark A.; Thompson, Lester D.R.; Agaimy, Abbas; Bishop, Justin A.
Abstract : Molecular analysis has reshaped the landscape of high grade sinonasal tumors by defining novel entities and identifying recurrent mutations in established tumor types. However, sinonasal teratocarcinosarcoma (TCS), a rare and aggressive tumor with intermixed teratomatous, carcinomatous, and sarcomatous elements, remains poorly understood. The multiphenotypic differentiation of TCS has engendered persistent controversy about its histogenesis and leads to diagnostic overlap with several other malignancies. In this study, we evaluated the molecular underpinnings of TCS to clarify its pathogenesis and diagnosis. We performed SMARCA4 immunohistochemistry (IHC) on 22 TCS and 153 other sinonasal tumors. We identified loss of SMARCA4 expression in 18 TCS (82%), including 15 (68%) with complete loss and 3 (14%) with partial loss. Although we also identified partial SMARCA4 loss in 1 of 8 SMARCB1-deficient sinonasal carcinomas (13%), SMARCA4 was intact in all other sinonasal carcinomas and neuroendocrine tumors. We then selected 3 TCS with complete SMARCA4 loss by IHC for a targeted next-generation sequencing panel that included 1425 cancer-related genes. We confirmed biallelic somatic inactivation of SMARCA4 without other known oncogenic mutations in these 3 cases. Overall, these findings suggest that SMARCA4 inactivation may be the dominant genetic event in TCS, expanding understanding of this gene's role in sinonasal tumorigenesis. They also raise the possibility that TCS is on a diagnostic spectrum with the newly described SMARCA4-deficient sinonasal carcinoma, blurring the lines between established and emerging sinonasal entities. In addition, SMARCA4 IHC may provide a useful adjunct for confirming a diagnosis of TCS in limited material.